Numerical simulation of two-phase flow by the finite element, discontinuous Galerkin methods and the level set method - Feistauer, Miloslav; Sváček, Petr (AIP conference proceedings, 2019)
The subject of the paper is the numerical simulation of two-phase flow of immiscible fluids. Their motion is described by the incompressible Navier-Stokes equations with piecewise constant density and viscosity. The interface between the fluids is defined with the level set method using a transport first-order hyperbolic equation. The Navier-Stokes problem is discretized by the Taylor-Hood P2/P1 finite elements combined with second-order BDF method in time. The transport level set problem is solved with the aid of the space-time discontinuous Galerkin method.